Developing programme and course learning outcomes - Chik, Abdul Rahman (2016)
Outcome-Based Education: University Quality Objectives, Program Educational Objectives (PEO), Program Learning Outcome (PLO), Course Learning Outcome (CLO). The objective of this workshop was to develop an OBE format of PEO, PLO and CLO for all UNISSA academic programmes. The workshop participants were guided through hands on approach by doing PLO and CLO for each programs.